Sensory and Omics approaches reveal the impact of heat treatment before fermentation on kiwi wine - Qiuyu Lan; Zhibo Yang; Lu Lin; Chuan Song; Junni Tang; Yuan Liu; Zonghua Ao; Suyi Zhang; Xin Du; Chenglin Zhu; Luca Laghi (npj Science of Food)
Abstract The study explores the effect of pre-fermentation heat treatment (PFHT) on the flavor and metabolomic profiles of kiwi wine (KW) derived from three kiwifruit cultivars. Six KW groups were involved, namely with/without PFHT for green (GWH/GW), yellow (YWH/YW), and red (RWH/RW) kiwifruit. E-tongue analysis effectively distinguished the taste profiles across these KW groups, identifying significant variations. A total of 97 volatile components were characterized using GC-MS and GC-IMS, 12 of them were identified as key volatile compounds based on a combination of t-tests (p < 0.05) and variable importance in projection (VIP) scores. GC-MS and GC-IMS results demonstrated that PFHT significantly altered volatile profiles, specifically decreasing ester content while increasing aldehyde levels in comparison to untreated samples. Furthermore, 71 non-volatile compounds were identified by 1H-NMR, with 10 key metabolites (p < 0.05, VIP > 1) contributing to the observed differences. PFHT notably influenced metabolomic profiles, particularly in carbohydrate and organic acid levels, displaying cultivar-specific differences. Green kiwifruit-derived KW showed the most pronounced sensitivity to PFHT, as reflected in both flavor and metabolic profiles. These findings offer valuable insights for optimizing KW production processes and scaling up industrial production.